HEMOGLOBIN LEVEL DIFFERENCES IN ATHLETE SPORTS DUE TO INTENSITY IN CENTRAL JAVA EDUCATION CENTER EXERCISE AND STUDENTS FOOT BALL (PPLP) WITH SALATIGA GUNUNGSARI FOOTBALL CLUB (GFC) - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2013)
Background: Exercise is physical movement exercises to strengthen and nourish the body weight, regular exercise can improve hemoglobin. From the results obtained obseravasi 30 sportsmen in Salatiga GFC and 30 sportsmen in PPLP do not get hemoglobin check up anda has different intensity.   Purpose: to determine differences in hemoglobin levels in athletes due to intensity of exercise.   Methods: This research is a comparative study. The population in this study was a sportsman in football PPLP and GFC Salatiga in Central Java. Sampling with purposive sampling with a sample of 30 athletes. To process the data used SPSS 16.0 for window programe with analysis whitney mann U-test.   The research results: Based on the results, the intensity of the sport in Salatiga PPLP weight (100%) with normal hemoglobin levels (93.3%) whereas in Salatiga GFC moderate exercise intensity (100%) with low hemoglobin levels (93.3%). bivariate analysis results are known p - value = 0.000 and the value of U - test 15,000.   Conclusion: There are differences in hemoglobin levels in athletes due to intensity of exercise. The more routine / high intensity exercise then able to increase hemoglobin levels sportsman.